Towards building silicon photonics: LiDAR chip - Navindran S/O Vijendran (Nanyang Technological University, 2024)
Light Detection and Ranging (LiDAR) is a system that is able to detect the surrounding environment in actual time and form high-definition 3-dimensional images [1]. Since its discovery, LiDAR has seen a sharp rise in popularity. However, the size of traditional LiDAR systems prevents it from being able to be used in a greater range of applications. Therefore, this project aims to make a LiDAR chip as small as possible, so as to enable LiDAR to be used in a greater range of applications. My primary focus for this project will be to work on the interconnection of Photonic Integrated Circuit elements and run simulations through Ansys Lumerical FDTD and INTERCONNECT software. The main aim of my task is to recreate the experimental setup as closely as possible on the Ansys INTERCONNECT module and analyze the simulation results.